Implementation of the MBKM Curriculum in the History Education Program - Nurul Yuliani; Zulkarnaen Zulkarnaen (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to: (1) examine the implementation of the Merdeka Belajar–Kampus Merdeka (MBKM) curriculum in the History Education Study Program; (2) identify the challenges in implementing the MBKM curriculum; and (3) provide solutions to address those challenges. This research employs a descriptive qualitative approach. Data were collected through interviews with the secretary of the History Education Department, lecturers, the MBKM curriculum development team, and students from the 2019, 2020, and 2021 cohorts. Relevant documents were also gathered. Data analysis followed the interactive model by Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that: (1) The implementation of the MBKM curriculum began with workshops on learning outcomes and curriculum preparation. The History Education Study Program refers to the 2020 MBKM curriculum as mandated by the Ministry of Education, Culture, Research, and Technology and UNY Rector’s Regulation No. 5 of 2020, which outlines three implementation models: (5-1-2), (6-1-1), and (6-0-2); (2) Challenges include the transition from online to offline learning, the academic information system (SIAKAD) not aligned with courses, course offerings not matching lecturers’ expertise, difficulty in grade conversion, and ineffective program socialization; (3) Solutions include standardizing courses across departments, blended learning, policy alignment at the university and faculty levels, improving communication through focus group discussions, establishing SOPs for grade conversion, and enhancing lecturer competencies through training.